Staging Plays at Shakespeare’s Globe: Then and Now - Thompson, Ann (Revista Alicantina de Estudios Ingleses, 2012)
The reconstruction of the Globe Theatre on London’s Bankside had historical accuracy as one of its aims, both in terms of the design and construction of the building itself and, more controversially, in terms of issues to do with performance. Scholars hoped the theatre would become a kind of laboratory in which they could test theories about how the plays might have been staged in Shakespeare’s time, and terms like ‘authenticity’ and ‘original practices’ were used. This essay discusses the sometimes patchy and unreliable evidence we have about ‘original practices’ from stage directions, dialogue and accounts of props and costumes; it also explores how the companies using Shakespeare’s Globe have used aspects of the building such as the yard, the space under the stage, the trapdoor and so on. And it provides examples of experiments with lighting and sound effects, and more radical ones with casting (gender, race and age) and original pronunciation. Finally, it argues that the theatre is not just a museum but a space for theatrical innovation, now as well as then.